THE EFFECT OF COMPETENCE AND CAREER DEVELOPMENT ON THE PERFORMANCE OF FUNCTIONAL OFFICIALS WITH WORK MOTIVATION AS AN INTERVENING VARIABLE - Farida Achmad; Susanti Widhiastuti; Jhoni Iskandar (Jurnal Scientia, 2023)
This study aims to determine the influence of competence, career development on the performance of functional officials with work motivation as an intervening variable in the environment of the Deputy for Environmental Management and Forestry Coordination of the Coordinating Ministry for Maritime Affairs and Investment. This type of research is associative research with a quantitative approach. The sampling method used is saturated sampling, so the sample of this study is all employees as many as 66 people with research instruments in the form of questionnaires. The analysis technique used is the Structural Equation Modeling - Partial Least Square test with the SMART-PLS 3.0 software tool. The results showed that: (1) competence has a positive and significant effect on the performance of functional officials; (2) career development has no effect on the performance of functional officials; (3) competence has a positive and significant effect on the work motivation of functional officials; (4) career development has a positive and significant effect on work motivation; (5) work motivation has a positive and significant effect on the performance of functional officials; (6) the effect of competence on the performance of functional officials with the mediation of work motivation is smaller statistical value of 2.573, compared to the direct effect of competence on the performance of functional officials without mediation of work motivation, in conclusion motivation is not able to mediate the effect of competence on performance; and (7) career development has a positive and significant effect on the performance of functional officials through the mediation of work motivation with a statistical value of t. amounted to 2,687.